"Archiving-as-a-Service". Influence of cloud computing on the archival theory and practice - Stančić, Hrvoje (Array, 2013)
The research is positioned in the context of the responsibility of archives to preserve important records in an increasingly changing technological environment, and focused on the impact of cloud solutions on archival theory and practice. Authors address several questions which they consider crucial for archival science and community. Results of the survey on the usage of private cloud are given. In view of that, the authors examine if the concept "Archiving-as-a-Service" will require redefinition of archival practice in the new technological and organizational context. Finally, they suggest the need for transition from postcustodial to "postcustodial 2.0" paradigm.